STUDI PERBANDINGAN PEMBELAJARAN KOOPERATIF MENGGUNAKAN MEDIA CHEMICAL DOMINO CARD DAN FLASH CARD - Nina Gusti; Amrul Bahar; Dewi Handayani (University of Bengkulu, 2017)
[COMPARISON STUDY OF COOPERATIVE LEARNING USING CHEMICAL DOMINO CARD AND FLASH CARD MEDIA] This study aims to measure differences in the results of chemistry learning between experimental class 1 classes that apply Chemical Domino Card learning media with experimental class 2 that apply Flash Card media at nomenclature of chemical compounds topics in class X IPA SMA Negeri 2 Kota Bengkulu at 2016 / 2017 academic year. Use of these two learning media is considered from the practicality, advantages, and effectivenes The type of research is a quasi experimental research with the population of all students of class X MIPA in SMA Negeri 2 Kota Bengkulu at 2016/2017 academic year , which a sample class is X MIPA E and X MIPA F. Implementation of research conducted by using two experimental class, X MIPA E which uses Chemical Domino Card media and class X MIPA F using Flash Card media. Data analysis used are mean value, homogeneity test, normality test and t test. The average value of posttest experimental class I for first and second meeting is 77,5 and 79,72, while for experiment class II is 86,94 and 88,61. Then t test is done by using difference of pretest and posttest value of student, which is obtained that both at first meeting and second t count> t table that is 2,44> 2,38081 (first meeting) and 2,81> 2,38081 (second meeting ). The results of this study indicate that there is a significant difference of student learning outcomes using Chemical Domino Card and Flash Card media on the nomenclature of chemical compounds